Bibliometric Analysis of a Comprehensive of Culture and Symbol in Character Animation during (2004–2024) - Yang, Chen; Jamali, Siti Salmi; Husain, Adzira (Journal of Ecohumanism, 2024)
The analysis of academic research on animated characters in the animation industry effectively summarises the current state of scholarly research on animated characters through a variety of software tools such as CiteSpace, VOS viewer, HistCite, and Bibliometrix analysis, and visually charts and formulates this data. Through study and research, it that the United States is (278) the most prolific country, and the United States has the highest intermediary centrality, as well as the most Centre National de la Recherche Scientifique (CNRS) and PEOPLES R CHINA are the most cited organizations and Countries/Regions with the highest intermediary centrality and Countries/Regions with the highest citation explosiveness, respectively. This study also suggests possible challenges and future directions in character design for animated characters.